Изменчивость активности пищеварительных ферментов клещей Varroa jacobsoni в онтогенезе - Барабанова, В.В. (Вестник зоологии, 1984)
Early nymphal stages are established to contain incomplete complex of enzymes under study. Amylase is absent during early premature stages, disappears at ecdysinal quiescence, and then gradually increases in females. Invertase activity gradually increases, reaching its maximum in adult females. Proteases increase their activity at ecdysinal quiescence and decrease in deutonymphs and adult females. Cellulolytic and chitolytic enzymes appear at quiescent stage Q₁₁₁ and increase activity in females. Males, though not feeding, have active hydrolases, except for chitolytic. Preimaginal stages, with their short longevity and low feeding activity, as compared to females, have lower negative effect on bees brood.